Percorso di inserimento del successore nell’azienda di famiglia: una valutazione dei possibili scenari - Sentuti, Annalisa (Piccola Impresa / Small Business, 2008)
This paper proposes a reflection on the possible introduction ways of successor in small and middle family firms. The study of fifteen business cases has suggested the elaboration of an interpretative scheme that has allowed to individualize five possible introduction profiles (traditionalists, precocious, alternative, graduates, consolidated)